Heart rate monitoring system design using LabVIEW / Nor Syahira Jak Jailani - Jak Jailani, Nor Syahira (2019)
The level of a person's health can be known through their heart rate. This pulse rate can be measured anywhere on the part of the body where the arteries beat to the surface of the skin. This project shows the methods of monitoring a person's heart rate by using embedded system and Lab VIEW technology. The main of objective this project is to study the effectiveness of Light Dependent Resistor (LDR) for heart rate monitoring. The hardware is developed on myRIO controller and designed in Lab VIEW. The LDR used in this system to measures changes in blood volume inside the patients' fingers. The amount of light absorbed by a finger depends on the changes of blood volume. There is a changes of heart rate when the blood volume in a finger changes. Since the measured output form LDR is too small, the system requires signal conditioning circuit to produce a usable sensor output. The heart rate monitoring system can be design low cost by using the Light Dependent Resistor. The LDR depends on the light. The accuracy of this sensor for heart rate monitoring is 93.66% in normal light. With additional light, the accuracy of this system increase from 93.66% to 98.08%. The error reduce by 4.42 percent by added external sources of light. In poor illumination, the error was to higher and this system cannot calculate the actual heart rate value.